The Historical Development of Islamic Education in Indonesia: Intersections of Culture and Politics - Suheri Suheri; Bedjo Sujanto (The Future of Education Journal, 2026)
Islamic education in Indonesia has a long history that is inseparable from the dynamics of culture and politics. Since the introduction of Islam to the Indonesian archipelago in the thirteenth century, educational institutions such as pesantren, surau, and madrasah have developed as centers for the transmission of Islamic knowledge and the formation of social and cultural identity. Islamic education has served not only as a medium for religious propagation (da'wah) but also as a cultural institution that has adapted to local traditions. At the same time, it has been shaped by political forces, including colonial rule, state policies, and changing power structures. During the Dutch colonial period, Islamic education was subject to restrictions because it was perceived as a potential political threat. Following Indonesia's independence, Islamic education was incorporated into the national education system, although it remained under state regulation. The Reform Era subsequently created greater opportunities for the development of Islamic education, enabling it to function both as a means of religious outreach and as an instrument influencing public policy. The interplay between cultural and political forces has made Islamic education in Indonesia distinctive, as it serves not only as a vehicle for learning but also as a space for negotiating identity, power, and culture. This study aims to analyze the historical development of Islamic education in Indonesia from cultural and political perspectives and to discuss its implications for contemporary Islamic education policy.